FOLD OF INCREASE DETERMINATION USING EFFECTIVE WELLBORE RADIUS - NITI DATON (NIM : 22210056), WIJOYO
Hydraulic fracturing has been used as a method to overcome the well skin problem. Since the classical paper of Mcguire - Sikora, about the effect of relative conductivity to well productivity, most fracturing job is done based on that paper. Many studies have been done ever since to determine the optimum fracture length in fracturing job but not yet concluded any valid mathematical model. This thesis offers an optional solution to determining the fracture length based on the chart from Mcguire - Sikora paper. Using Prats method of effective wellbore radius and correction for , the result is similar to the McGuire Ã‚Â– Sikora chart with accuracy level of 2% maximum margin of error.